Minimalisasi Penyebaran COVID 19 Pada Lingkungan Pesantren, Sekolah dan Puskesmas Melalui Bantuan Alat Wastafel Portabel - Azwar Hayat; Andi Erwin E. Putra; Lukmanul Hakim Arma; Hairul Arsyad; Muhammad Syahid; Novriany Amaliyah; Gerard A. Duma; Asriadi Sakka (Faculty of Engineering UNHAS, 2020)
The level of the spread of covid-19 in Indonesia continues to increase, the number of people who have been confirmed positive for Covid-19 is 55,092 people with a death toll of 2,805. South Sulawesi is in the third rank of a province with a high level of spread with a positive confirmed number of Covid-19 of 4,995 people and a death toll of 164 people (data as of 29 June 2020). To reduce the high spread in South Sulawesi province, various preventive measures have been taken. One of the most effective preventive measures is to always wash your hands with soap. Soap has been shown to effectively damage the outer protein layer of Covid-19 and in the end can kill the virus. In this community service, the aim is to provide portable sink equipment assistance and at the same time to socialize the prevention of the spread of Covid-19 through banners at Islamic boarding schools, puskesmas and schools in the Gowa district area. This activity will be carried out as an effort to prevent the spread of Covid-19 in Islamic boarding schools, schools and health centers in entering the current “new normal” period.